Shopping : 26 art installations in 26 shops throughout Soho. (New York : Deitch Projects, 1996)
Grigely, Joseph ; Reiss, Trudie ; Lum, Ken ; Beecroft, Vanessa ; Hirakawa, Noritoshi ; Anderson, Jim ; Fleury, Sylvie ; Gordon, Douglas ; Samore, Sam ; Wurm, Erwin ; Kaplowitz, Jane ; Lévêque, Claude ; Oppenheim, Kristin ; Brinch, Jes ; Plenge Jakobsen, Henrik ; Hatoum, Mona ; Tin Nyo, Elaine ; Chen Zhen ; Havel, Joseph ; Green, Gregory ; Jugnet, Anne Marie ; Dector, Michel ; Dupuy, Michel ; Manetas, Miltos ; Orta, Lucy ; Grennan & Sperandio ; Grennan, Simon ; Sperandio, Christopher ; Sinclair, Ross ; Hayes, Paula
Shopping : 26 art installations in 26 shops throughout Soho, Deitch Projects, New York, september 5 to 21 1996
Engels
boek